Alpha-linolenic acid protects against lipopolysaccharide-induced acute lung injury through anti-inflammatory and anti-oxidative pathways. (May 2020) - Zhu, Xuejiao; Wang, Bing; Zhang, Xinyi; Chen, Xia; Zhu, Jiali; Zou, Yun; Li, Jinbao
Abstract: Alpha-linolenic acid (ALA), an important component of polyunsaturated fatty acids (PUFAs), possesses potent anti-inflammatory properties. To date, the effects of ALA on acute lung injury (ALI) remains unknown. This study was designed to investigate the potential protective effects of ALA on LPS-induced ALI and the underpinning mechanisms. An animal model of ALI was established via intratracheally injection of lipopolysaccharide (LPS, 1 mg/kg). We found that lung wet/dry weight ratio and protein concentration in Bronchoalveolar lavage fluid (BALF) were dramatically decreased by ALA pretreatment. Treatment with ALA significantly alleviated the infiltration of total cells and neutrophils, while increased the number of the macrophages. ALA significantly inhibited the secretion of proinflammatory cytokines including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interleukin-1β (IL-1β) and increased anti-inflammatory cytokine. Moreover, we found that the levels of myeloperoxidase (MPO) and malondialdehyde (MDA) were highly increased in LPS-induced ALI, while the activities of glutathione (GSH) and superoxide dismutase (SOD) were decreased, which were reversed by ALA. ALA attenuated LPS-induced histopathological changes and apoptosis. Furthermore, ALA significantly inhibited the phosphorylation of IκBα and NF-κB (p65) activation in ALI. ALA showed anti-inflammatory effects in mice with LPS-induced ALI. NF-κB pathway may be involved in ALA mediated protective effects. Highlights: ARDS are the major causes of respiratory failure in the intensive care unit worldwide. ALA is one of the two essential fatty acids, which are indispensible for health. ALA showed anti-inflammatory and anti-oxidative effects in mice with LPS-induced ALI. NF-κB pathway may be involved in ALA mediated protective effects.